Oncological Outcome of Surgically Resected Sternal Tumors, 16 Years’ Experience - Abdelrahman, Abdelrahman; Ismail, Mourad; Ghaly, Galal; Abulkheir, Iman Loay; Hanafy, Ayman (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Tumors of the sternum are rare and can develop from primary bone pathology or through metastatic spread. Sternal resection with immediate reconstruction of the anterior chest wall defect was recommended for both primary and secondary sternal tumors as curative treatment. AIM: The purpose of our study was to examine the perioperative outcomes, recurrence rate, and OS in patients undergoing partial, subtotal, and total sternectomy. METHODS: We retrospectively reviewed our experience with sternal resections in 29 patients during a 16-year period. The purpose of our study was to examine the perioperative outcomes, recurrence rate, and overall survival (OS) in patients undergoing partial, subtotal, and total sternectomy. RESULTS: We found that 5-year OS was 26.0%, Univariate analysis of predictors of survival revealed that, there was a trend toward prolonged 5-year survival at R0 resection (35.5% vs. 0%, p = 0.058). Post resection defect size associated with prolonged 5-year OS (42.1% vs. 0%, p < 0.001). The absence of post-operative complications associated with prolonged 5-year OS (40.4% vs. 0%, p = 0.012), with special attention to absence of post-operative flail chest which was associated with prolonged 5-year OS (36.2% vs. 0%, p < 0.001). On multivariable analysis, R0 resection (HR, 3.692 [95% CI, 1.190–11.456], p = 0.024) and absence of post-operative flail chest (HR, 52.204 [95% CI, 5.908–461.289], p < 0.001) were associated with improved OS. CONCLUSIONS: We have shown that sternal resection of benign and primary malignant tumors can yield long-term survival. The completeness of resection and absence of postoperative flail chest are the strongest predictors of survival.